Mechanism Underlying the Formation of a Cluster of Metabolic Syndrome - Kseneva, Svetlana I.; Borodulina, Elena Valentinovna; Udut, Vladimir Vasilievich; Fisenko, Vladimir Petrovich (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: The concept of metabolic syndrome (MetS) as a cluster of risk factors of type 2 diabetes and cardiovascular diseases has undergone some evolutionary transformations over the past years. Integrating the autonomic dysfunction into the pathogenesis of MetS creates the possibility of including a range of nosologies affecting treatment and clinical manifestations of pathologies belonging to MetS into the MetS cluster. The purpose of this work is to determine the involvement of autonomic dysfunction in the pathogenesis of associated pathological conditions in patients and MetS. Methods: A cross-sectional study was conducted. The sample consisted of 158 patients with metabolic syndrome. The patients underwent a physical examination, including BMI; a blood chemistry test with the determination of the hormonal status (insulin, testosterone, dihydrotestosterone); a 24-hour monitoring of blood pressure (BP); an assessment of heart rate variability; studies showing the presence of gastric reflux (#128;Ц#157;-measurement) or its damaging impact (endoscopy); men were tested with the IPSSQOL questionnaire and underwent transrectal ultrasound of the prostate and ultrasound of the bladder. Results: It is revealed that because of MetS, the occurrence of cardiac autonomic neuropathy reaches 37.5%. Some features of gastroesophageal reflux disease in patients with MetS are shown. Regurgitation prevails in the structure of complaints. In case of fibrogastroduodenoscopy, an endoscopynegative form of the disease occurs in 38%. According to the data of daily pH-measurement, when DeMeester score is high, in the supine position, 25% of the time accounts for alkaline reflux (#128;Ц#157; > 7). It is found out that young men experience the enlargement of prostate volume and size; according to the IPSS questionnaire, the scores correspond to the initial manifestations of hyperplastic diseases of the prostate gland due to insulin resistance and normal level of androgens. Conclusion: The paper demonstrates that the autonomic dysfunction of the nervous system (on a par with insulin resistance) is the main link in the development of MetS. This provides the basis for including the mentioned states – cardiac autonomic neuropathy, lower urinary tract symptoms, and gastroesophageal reflux disease – into the MetS cluster.
Keywords: autonomic dysfunction